Heritage questing with Virginia Woolf: UCL Institute of Archaeology's 'spirit of place' and new pedagogies of the pandemic. Issue 1 (30th December 2021) - Butler, Beverley; Francis, David; Pavey, Ellen
Abstract : page_99 other This article charts a particular journey of discovery – that of 'heritage questing with Virginia Woolf'. We explore how, against the backdrop of COVID-19, the Master's in Cultural Heritage Studies (MACHS) adopted and adapted Virginia Woolf as an efficacious 'ancestor figure' around which staff and students were able to grasp, engage with, articulate and try to understand the extraordinary experiences and challenges faced throughout the academic year. Woolf emerged as the shared conduit and portal by which MACHS in 'diaspora' could imaginatively connect with, collectively tap into and add new layers to the Institute of Archaeology (IoA)'s 'spirit of place' in Bloomsbury. In what follows, our article draws on a co-ethnography of these experiences which, in turn, we juxtapose alongside Virginia Woolf's own literary insights. Writ large, our journey sees us critically reflect upon attempts to navigate the unknown currents and trajectories of living, teaching and learning in times of coronavirus within which Woolf emerged as a lighthouse of sorts. Writ larger still, we see our quest as a means to grasp the 'new pedagogies of the pandemic' that materialised as an outcome of the impacts and experiences of coronavirus. Ultimately these were also seized upon as a means of taking page_100 other forward the shared promise of fulfilment, in terms of shaping such quests into liveable presents and better futures as well as adding new layers to the IoA's stratigraphy.